Religiosity of Citapen Youth: The Role Of Majlis Ta'lim In Purwakarta District - Muh. Faysal; Nadya Yulianty (AMIN: International Journal of Islamic Education and Knowledge Integration, 2023)
This study aims to describe the role of majlis ta'lim in improving the religiosity of teenagers citapen sukajaya village sukatani district purwakarta. The research method used is descriptive qualitative research with data collection techniques through interviews. The results of the study that the role of majlis ta'lim in shaping the religiosity of adolescents requires several ways. In accordance with what was conveyed by the informant as the supervisor of majlis ta'lim, that the role of maslis ta'lim here is by forming and managing a good program to develop youth religiosity, including by forming IRMA or mosque youth bonds, forming Al-khoiriyah tahfidz houses, this program has proven successful in developing youth religiosity in Citapen Sukajaya Village Sukatani Purwakarta Regency.